Eye irrigation as a first-line treatment and diagnostic method for emergency department patients who complain of ocular foreign bodies - Hung-Da Chou (Nature Portfolio, 2021)
Abstract This prospective study aimed at determine whether eye irrigation removes ocular foreign bodies (FBs) and whether ocular pain predicts FBs. Emergency department patients complaining of ocular FBs were enrolled. In the irrigation group (n = 52), pain was evaluated with a visual analog scale before and after irrigation, and the presence of FBs was determined under a slit-lamp. In the nonirrigation group (n = 27), the evaluations were performed upon arrival. The corneal FB retention rate was found significantly lower in the irrigation (13/52, 25%) than in the nonirrigation groups (13/27, 48%; P = 0.04). After irrigation, those without FBs had more patients experiencing pain reduction (67%) compared to those with retained FBs (46%; P = 0.14) and had a greater magnitude of change in pain score (mean ± SD, − 2.6 ± 2.7 vs. − 0.7 ± 1.4; P = 0.02). An improvement in ocular pain score ≥ 5 points after irrigation predicted the absence of FBs with a negative predictive value of 100%. Eye irrigation significantly lowered corneal FB retention; if ocular pain decreased considerably, the probability of retained FBs was low, making irrigation-associated pain score reduction a feasible diagnostic method to exclude FB retention without needing specialized ophthalmic examinations.